Proving Einstein right : the daring expeditions that changed how we look at the universe - Gates, S. James, Jr.; Pelletier, Cathie (New York : PublicAffairs, 2019)
"In 1911, a nearly unknown German-born theoretical physicist named Albert Einstein had developed his theory of relativity, but hadn't yet been able to prove it. The only way to do that was through the clear view and measurement of a solar eclipse. In May of 1919, one of the longest total solar eclipses of the 20th century was visible for almost seven minutes in the Southern Hemisphere"--
Includes bibliographical references (pages 326-338) and index.
Keywords: Einstein, Albert, -- 1879-1955.; Solar eclipses -- 1919.; Total solar eclipses; Relativity (Physics)